Microstructure and mechanical properties of laser indirect brazed titanium/steel composite joint with a CuZn filler metal. Issue 16 (2nd November 2022) - Zeng, Haoyuan; Yu, Deshui; Zhang, Yan; Zhou, Jianping; Chen, Yankun
Abstract : In this study, the research on the laser welding TC4 alloy and stainless steel dissimilar metals with composite welding mechanism was investigated. Dissimilar joints of TC4 alloy and stainless steel were generated by indirect laser brazing. Moreover, in order to further explored the bonding mechanism of joints, CuZn metal was used as the filler material to study the welding process of TC4 alloy and 304 stainless steel with indirect laser brazing and transition section. The filler was extruded into metal droplets due to the metal expansion during laser welding, which increased the tightness of the joint. With the increase of heat input, the reaction between the filler and the base metals on both sides was more intense. In addition, the tensile strength reached 210 MPa (41% of stainless steel) when the laser power was 624 W.